2017
DOI: 10.1097/mpg.0000000000001323
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of Diarrhea, Nutritional Outcomes, and Novel Intestinal Biomarkers in Tanzanian Infants

Abstract: Objective Diarrheal diseases are a leading cause of morbidity and mortality worldwide, but the etiology of diarrhea and its relationship to nutritional outcomes in resource-limited settings is poorly defined. We sought to determine the etiology of community-acquired diarrhea in Tanzanian infants, and to assess the association with anthropometrics and novel intestinal biomarkers. Methods A convenience sample of infants in a trial of zinc and/or multivitamin supplementation in Tanzania was selected. Subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
(58 reference statements)
4
3
0
Order By: Relevance
“…The groups were comparable regarding age and gender, more vomiting in the diarrhea group compared to the control group further confirmed clinically apparent gastroenteritis within the diarrheal group. Our findings confirmed a high prevalence of bacterial and protozoan intestinal infections previously reported in Tanzanians [ 18 , 19 ]. Among the identified enteropathogenic protozoa, G .…”
Section: Discussionsupporting
confidence: 92%
“…The groups were comparable regarding age and gender, more vomiting in the diarrhea group compared to the control group further confirmed clinically apparent gastroenteritis within the diarrheal group. Our findings confirmed a high prevalence of bacterial and protozoan intestinal infections previously reported in Tanzanians [ 18 , 19 ]. Among the identified enteropathogenic protozoa, G .…”
Section: Discussionsupporting
confidence: 92%
“…Rotavirus and bacteria coinfection was reported among diarrhoeic children in this study, with rotavirus and DEC coinfection being the most observed, rotavirus with Shigella coinfection was the next bacteria coinfection between Shigella and Salmonella was observed as the least co-infection in the study. Since there is no recent study in the country that has investigated the aetiology of diarrhoea from viral and bacterial origin to compare the result with, this result is similar to previous findings in developing countries where the combined infection between viral and bacterial etiologies of diarrhoea has been reported [ 21 , 22 , 24 , 36 ]. However, co-infection had no statistical significant on the severity of diarrhoea (P = 0.523).…”
Section: Discussionsupporting
confidence: 87%
“…The introduction of a highly effective rotavirus vaccine decreased overall incidence of rotavirus diarrhea. Thus, Crypto-sporidium is expected to become the leading cause of childhood diarrhea worldwide [5][6] . Few pharmaco-logical interventions are available for Cryptosporidium infection.…”
Section: Introductionmentioning
confidence: 99%